Mímesis verbal amazónica en la cuentística infantil y juvenil de Francisco Izquierdo Ríos - Muñoz Cuchca, Amado (2025)
Francisco Izquierdo Ríos (1910-1981), a distinguished Peruvian writer from the Amazon region, is recognized for his collection of children's and young adult stories. Despite their educational and cultural value, his works have been marginalized within the national school curriculum. This study qualitatively analyzes his literary production, highlighting his pedagogical contributions (moral values, reader formation) and the use of Amazonian verbal mimesis (imitation of regional speech). A biographical-narrative method and content analysis of 43 stories were employed, complemented by semi-structured interviews with specialists and family members. The results show that his literature combines didactic intent with aesthetic quality, rescues Amazonian oral tradition through idioms and local dialects, and can be used as a pedagogical resource to promote reading. The discussion emphasizes that his work reflects Amazonian culture and provides a valuable contribution to the Peruvian educational curriculum in terms of interculturality and comprehensive education. The study concludes that it is essential to reassess and incorporate Izquierdo Ríos' stories into school programs to enrich the educational experience and preserve cultural heritage.